2020
DOI: 10.1200/jco.2020.38.29_suppl.18
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to increase adherence to ASCO Choosing Wisely recommendations for breast cancer surveillance at community clinics.

Abstract: 18 Background: ASCO 2012 Choosing Wisely recommends against serum tumor marker tests and advanced imaging for breast cancer survivors who are asymptomatic for recurrence. Our pilot aimed to measure and raise adherence to this recommendation through a patient video at regional community clinics. Methods: Eligibility for study included patients with 1+ long-term follow-up visit within 3 months of end of treatment in the pre- or post-intervention period: Clinic tumor registries were queried for stage I-IIIA brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Eleven studies described interventions to support compliance with guidelines on diagnosis and treatment [ 41 , 43 , 52 , 56 , 64 70 ], 9 focused on treatment only [ 38 – 40 , 42 , 47 49 , 62 , 63 ], 5 on diagnosis only [ 45 , 51 , 58 – 60 ], and 7 on screening [ 36 , 37 , 46 , 50 , 54 , 57 , 61 ]. Six studies were randomized controlled trials [ 37 , 45 , 50 , 51 , 54 , 60 ], four were non-randomized controlled trials [ 46 , 57 , 58 , 63 ], eight non-controlled before-after studies [ 42 , 49 , 53 , 55 , 59 , 62 , 65 , 69 ], one prospective cohort study , three cross-sectional studies [ 44 , 47 , 56 ], one mixed-methods [ 36 ] and twelve case studies [ 38 – 41 , 43 , 48 , 52 , 61 , 64 , 66 – 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven studies described interventions to support compliance with guidelines on diagnosis and treatment [ 41 , 43 , 52 , 56 , 64 70 ], 9 focused on treatment only [ 38 – 40 , 42 , 47 49 , 62 , 63 ], 5 on diagnosis only [ 45 , 51 , 58 – 60 ], and 7 on screening [ 36 , 37 , 46 , 50 , 54 , 57 , 61 ]. Six studies were randomized controlled trials [ 37 , 45 , 50 , 51 , 54 , 60 ], four were non-randomized controlled trials [ 46 , 57 , 58 , 63 ], eight non-controlled before-after studies [ 42 , 49 , 53 , 55 , 59 , 62 , 65 , 69 ], one prospective cohort study , three cross-sectional studies [ 44 , 47 , 56 ], one mixed-methods [ 36 ] and twelve case studies [ 38 – 41 , 43 , 48 , 52 , 61 , 64 , 66 – 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies were randomized controlled trials [ 37 , 45 , 50 , 51 , 54 , 60 ], four were non-randomized controlled trials [ 46 , 57 , 58 , 63 ], eight non-controlled before-after studies [ 42 , 49 , 53 , 55 , 59 , 62 , 65 , 69 ], one prospective cohort study , three cross-sectional studies [ 44 , 47 , 56 ], one mixed-methods [ 36 ] and twelve case studies [ 38 – 41 , 43 , 48 , 52 , 61 , 64 , 66 – 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the campaign provides education modules, which include five questions patients should ask providers before receiving any test, treatment or procedure, with the final question focused on the cost of treatment and the availability of less expensive alternatives. A recent study examining the use of serum tumor marker tests for breast cancer survivors who are asymptomatic found that when patients were given a Choosing Wisely educational module on the guidelines, the rates of adherence to the recommendations increased [59]. Other research indicates that such SDM approaches result in patients choosing less invasive -and less costly -treatments [60].…”
Section: Shared Decision-making and Communicationmentioning
confidence: 99%